Cytogenetic comparison of Podocnemis expansa and Podocnemis unifilis: a case of inversion and duplication involving constitutive heterochromatin - Gunski,Ricardo José (2013)
Podocnemis expansa and P. unifilis present 2n = 28 chromosomes, a diploid number similar to those observed in other species of the genus. The aim of this study was to characterize these two species using conventional staining and differential CBG-, GTG and Ag-NOR banding. We analyzed specimens of P. expansa and P. unifilis from the state of Tocantins (Brazil), in which we found a 2n = 28 and karyotypes differing in the morphology of the 13th pair, which was submetacentric in P. expansa and telocentric in P. unifilis. The CBG-banding patterns revealed a heterochromatic block in the short arm of pair 13 of P. expansa and an interstitial one in pair 13 of P. unifilis, suggesting a pericentric inversion. Pair 14 of P. unifilis showed an insterstitial band in the long arm that was absent in P. expansa, suggesting a duplication in this region. Ag-NORs were observed in the first chromosome pair of both species and was associated to a secondary constriction and heterochromatic blocks.